Revision of the "euryglossiform" species of the Afrotropical bee genus Scrapter Lepeletier & Serville, 1828 (Hymenoptera: Apoidea: Colletidae) - Michael Kuhlmann (European Journal of Taxonomy, 2014)
The South African endemic bees of the "euryglossiform" species of the genus Scrapter Lepeletier & Serville, 1828 are revised and illustrated. The species-group is defined for the first time and comprises 20 species, 16 of which are described here as new: Scrapter exiguus sp. nov. ♀, ♂, S. gessorum sp. nov. ♀, S. inexpectatus sp. nov. ♀, S. luteistigma sp. nov. ♀, ♂, S. minutissimus sp. nov. ♂, S. minutuloides sp. nov. ♀, S. minutus sp. nov. ♀, S. nanus sp. nov. ♀, ♂, S. nigerrimus sp. nov. ♀, S. nigritarsis sp. nov. ♀, S. papkuilsi sp. nov. ♀, ♂, S. punctatus sp. nov. ♀, ♂, S. pygmaeus sp. nov. ♀, S. roggeveldi sp. nov. ♀, ♂, S. spinipes sp. nov. ♀, ♂ and S. ulrikae sp. nov. ♀, ♂. For S. acanthophorus Davies, 2005 and S. sittybon Davies, 2005 the female is here described for the first time. A key to all species is provided.